Resistance to compression of weakened roots subjected to different root reconstruction protocols - Zogheib, Lucas Villaça; Saavedra, Guilherme de Siqueira Ferreira Anzaloni [UNESP]; Cardoso, Paula Elaine [UNESP]; Valera, Márcia Carneiro [UNESP]; de Araújo, Maria Amélia Máximo [UNESP] (FapUNIFESP (SciELO), 2011)
Objective: This study evaluated, in vitro, the fracture resistance of human non-vital teeth restored with different reconstruction protocols. Material and methods: Forty human anterior roots of similar shape and dimensions were assigned to four groups (n=10), according to the root reconstruction protocol: Group I (control): non-weakened roots with glass fiber post; Group II: roots with composite resin by incremental technique and glass fiber post; Group III: roots with accessory glass fiber posts and glass fiber post; and Group IV: roots with anatomic glass fiber post technique. Following post cementation and core reconstruction, the roots were embedded in chemically activated acrylic resin and submitted to fracture resistance testing, with a compressive load at an angle of 45° in relation to the long axis of the root at a speed of 0.5 mm/min until fracture. All data were statistically analyzed with bilateral Dunnett's test (α=0.05). Results: Group I presented higher mean values of fracture resistance when compared with the three experimental groups, which, in turn, presented similar resistance to fracture among each other. None of the techniques of root reconstruction with intraradicular posts improved root strength, and the incremental technique was suggested as being the most recommendable, since the type of fracture that occurred allowed the remaining dental structure to be repaired. Conclusion: The results of this in vitro study suggest that the healthy remaining radicular dentin is more important to increase fracture resistance than the root reconstruction protocol.
Keywords: Compressive strength; Nonvital tooth; Permanent dental restoration; Post and core technique; Tooth fractures; Tooth root